Food Safety on the Farm: Produce Safety Rule and Good Agricultural Practices – Field Sanitation: FSHN10-12/FS160, rev. 3/2019 - Lepper, Jessica A.; De, Jaysankar; Pabst, Christopher; Sreedharan, Aswathy; Goodrich Schneider, Renée M.; Schneider, Keith R. (EDIS, 2019)
Good Agricultural Practices (GAPs) and Good Handling Practices (GHPs) encompass the general procedures that growers, packers, and processors of fresh fruits and vegetables should follow to ensure the safety of their product. GAPs usually deal with preharvest practices (i.e., in the field), while GHPs cover postharvest practices, including packing and shipping. This 5-page fact sheet covers harvest practices associated with sanitation in the field, including basic principles for microbial food safety and control of potential hazards. This major revision is a part of the Food Safety on the Farm series and was written by Jessica Lepper, Jaysankar De, Christopher Pabst, Renée Goodrich-Schneider, and Keith Schneider and published by the UF/IFAS Food Science and Human Nutrition Department. http://edis.ifas.ufl.edu/fs160